Possible educations: teaching and research through experimentation (Revista de Ensino em Artes, Moda e Design, 2024)
Through this interview, Professor Marilda Oliveira de Oliveira talks about her journey as a researcher, explaining the path that led her to her current investigations. With regard to their areas of interest, we seek to identify their possible relationships with basic education, going through the idea of “possible educations'' to promote the paths of teaching and research that, at times, are built on subversion.
Keywords: education in Visual Arts; research; experimentation